The STR Line-of-Sight Pointing and Acquisition in the Gravitational Wave Detection Interstellar Laser Link - Sibo Liang; Xin Zhao; Tong Wang; Cheng Han (IEEE Photonics Journal)
In space gravitational wave detection, the establishment of inter-satellite laser links is a prerequisite for the smooth execution of the detection mission. The TianQin space gravitational wave detection Program uses star tracker (STR) and a charge coupled device (CCD)/ quadrant photodiode (QPD) to complete the construction of a bidirectional satellite laser link to achieve high-precision laser acquisition and tracking control. In order to solve the problem of the initial acquisition uncertainty cone being too large, the coordinate transformation matrix principle is applied to complete the STR line-of-sight calibration, so as to reduce the size of the acquisition uncertainty cone. The probability density distribution function of the uncertainty cone and the size of the uncertainty cone were determined based on the Monte Carlo simulation method. The average scanning acquisition time simulation calculation is completed based on the spiral scanning principle. The simulation results show that the size of the acquisition uncertainty cone after STR line-of-sight calibration is reduced by 73.24% compared with the original acquisition uncertainty cone, and the scanning acquisition time is reduced by 92.8% compared with the original scanning acquisition time.